SMYD2 inhibitors have no effect in improving non-alcoholic steatohepatitis in mice - Yang, Lanzexin; Zhuo, Shixuan; Zhu, Xinyu; Zhang, Xinhui; Wang, Zinan; Chen, Yan (Frontiers in Endocrinology, 2025)
IntroductionNonalcoholic steatohepatitis (NASH), characterized by progressive liver injury, inflammation, and fibrosis, is a leading chronic liver disease worldwide. Pharmacotherapy for NASH is thus urgently needed. Through a strategy of in vivo lineage tracing, it was recently discovered that deletion of a protein methyltransferase SMYD2 has a protective role in hepatic steatosis. In this study, we evaluated the potential therapeutic effect of two SMYD2 inhibitors AZ505 and LLY-507 in a mouse NASH model.MethodsThe mouse NASH model was induced by a choline-deficient, L-amino acid-defined, high-fat diet (CDAHFD) for 12 weeks. SMYD2 inhibitors AZ505 and LLY-507 were administered in the last 4 weeks at a dose of 10 mg/kg by intraperitoneal injection three times per week. A series of biochemical and histological analyses were conducted to determine the therapeutic potential of SMYD2 inhibitors.ResultsThe inhibitory effect of AZ505 and LLY-507 on histone methylation was confirmed with liver samples. CDAHFD was able to induce marked liver fibrosis and inflammation in the mice. However, treatment of the mice with AZ505 and LLY-507 failed to show any improvement in NASH scores, liver damage, liver fibrosis, macrophage infiltration, or hepatic inflammation in mice.DiscussionIn conclusion, our findings suggest that SMYD2 inhibition is not an effective strategy to alleviate NASH at least in mice.